A Protocol of a Guideline to Establish the Evidence Ecosystem of Acupuncture - Wang, Qin; Li, Nian; Li, Juan; He, Ying; Li, Yuxi; Zhong, Dongling; Liu, Xiaobo; Fan, Jin; Jin, Rongjiang; Kang, Deying; Zhang, Yonggang (Frontiers in Medicine, 2022)
This is a protocol for developing a guideline to establish the evidence ecosystem of acupuncture. It describes all steps that will be followed in line with the World Health Organization Handbook for Guideline Development and the Reporting Items for practice Guidelines in Healthcare (RIGHT). The key steps included guideline protocol development, guideline registration, systematic review of acupuncture evidence issues, systematic review of methods for establishing evidence ecosystem, survey of acupuncture stakeholders regarding potential acupuncture evidence issues, development of potential items for guidelines, Delphi method for guideline item development, consensus meeting, drafting guideline, peer review, approval, and publishing. This future guideline will help to establish evidence ecosystem of acupuncture, which will facilitate the application of acupuncture in clinical practice.